Perceptions of Good Jobs : Analytical Report--Jianyang, China Sichuan - Zhang, Huafeng (World Bank, Washington, DC, 2013)
This study describes how jobs are perceived in Jianyang, China Sichuan, by exploring beyond the earnings, health benefits, and pension plans that characterize a “good job” to focus on the features that increase living standards, productivity growth, and social cohesion. Tremendous changes in the Chinese labor market have altered the perceptions and attitudes of people toward their work. The labor force participation in Jianyang is 62 percent, with men’s rate exceeding that of women, and high education strongly correlating with labor force participation. In both urban and rural areas, households with a higher number of working adults and wage-earners are better off, and strong linkages exist between job stability and benefits.Overall there is a low degree of job satisfaction, with the highest satisfaction found among wage workers. While jobs in Jianyang consist mainly of manual labor—dominated by routine work—a “good job” in the sense of a higher degree of meaningfulness requires a shift from manual to more cognitive work, from routine to more creative tasks. Employment contributes to a very high level of trust in family, neighbors, and friends. Wage workers also indicated lower confidence in institutions.